2019
DOI: 10.1016/j.ijcard.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Long term prognostic importance of late gadolinium enhancement in first-presentation non-ischaemic dilated cardiomyopathy

Abstract: Long term prognostic importance of late gadolinium enhancement in first-presentation non-ischaemic dilated cardiomyopathy. Ijca (2019),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Furthermore, Lehrke et al have shown that NIDCM can be confirmed by cMRI-determined LV midwall fibrosis [23]. In our study, the incidence of LGE in NIDCM was similar with other studies [8,24] and, in addition, we demonstrated that LGE was an independent predictor of MACEs. Similarly, in patients with NIDCM, Gulati et al showed that the presence of mid-wall LGE was an independent predictor for outcome and improved risk stratification beyond LVEF [9].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Lehrke et al have shown that NIDCM can be confirmed by cMRI-determined LV midwall fibrosis [23]. In our study, the incidence of LGE in NIDCM was similar with other studies [8,24] and, in addition, we demonstrated that LGE was an independent predictor of MACEs. Similarly, in patients with NIDCM, Gulati et al showed that the presence of mid-wall LGE was an independent predictor for outcome and improved risk stratification beyond LVEF [9].…”
Section: Discussionsupporting
confidence: 91%
“…(18) LGE imaging is a sensitive, speci c and reproducible method used in assessing focal myocardial brosis and predicting prognosis in patients with ischemic and nonischemic cardiomyopathies. (25)(26)(27) In this study, LGE was evident in all the patients with con rmed RHD.…”
Section: Discussionsupporting
confidence: 51%
“…Thirty studies with a total of 7541 patients reported major ventricular arrhythmic events, which occurred in 810 patients (10.7%) 4 , 9 , 16 19 , 25 28 , 31 33 , 35 , 37 39 , 42 44 , 46 , 51 , 57 , 60 , 62 , 63 , 66 , 68 , 71 . The pooled OR and rates of major ventricular arrhythmic events were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies with a total of 5807 patients reported cardiovascular mortality, which occurred in 734 patients (12.6%) 9 , 10 , 17 , 21 , 29 31 , 33 , 35 , 37 40 , 43 , 44 , 48 , 51 , 57 , 58 , 62 , 63 , 66 , 68 , 71 . The pooled OR and rates of cardiovascular mortality were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%